Detection of the Resistance of Parasite to Sulfadoxine-pyrimethamine Drugs and msp-2 Genotyping as A Baseline in Developing Malaria Vaccine with Ionizing Radiation - Mukh Syaifudin; Harry Nugroho Eko Surniyantoro; Teja Kisnanto; Antonius Oktavian; Puji Budi Setia Asih (Jurnal Ilmiah Aplikasi Isotop dan Radiasi, 2019)
Polymorphism or mutation in specific genes of P. falciparum and P. vivax is involved in the resistance to sulfadoxine-pyrimethamine (SP) antimalarial drug. On the other hand msp-2 gene plays an important role in drug resistance related genotyping. This study was undertaken as a basic information in assessing the urgent of development of malaria vaccine that can be created by ionizing radiation. Deoxy ribonucleic acid (DNA) of blood from malaria infected outpatients in Dok II Hospital of Jayapura for November 2014 period was amplified using nested polymerase chain reaction (PCR) and followed by restriction fragment length polymorphism (RFLP) analysis to determine the polymorphisms of SP resistance. Among 15 samples tested for dhfr gene, 9 (60%) and 8 (53%) samples showed positive result for polymorphisms in JR78/79 and F/108DH primers, respectively. For dhps gene by using JR84/85 and L/L primers 7 samples were positive mutant. These frequencies are lower compared to results of other research. Of these 15 samples examined, 3 had 3D7 alleles and 4 had FC27 alleles of the msp2 gene. No mutated S1105 and S1240 alleles and 6 mutant VDT alleles were found in P. vivax. It can be concluded that the resistance of parasites to SP was quite high, indicating the highly urgency to develop malaria vaccine.